Caracterización parcial de un potexvirus aislado de pitahaya amarilla (Selenicereus megalanthus) afectada por mosaico en Colombia - Reichel, Helena; Pérez, R.; Martínez, A.K.; Sedano Cruz, RE; Cuervo Ibáñez, Maritza; Arroyave, José A.; Morales, Francisco José (2002)
Yellow pitahaya (Selenicereus megalanthus) plants showing mosaic symptoms, from the locality of Arbeláez, Cundinamarca, Colombia, were shown by electron microscopy to contain viral-like filamentous particles of ca. 476 x 10 nm. IC-RT-PCR amplified a fragment of ca. 370 base pairs, showing a 94% amino acid homology to the coat protein of Cactus virus X (CVX). This is the first report of CVX infecting yellow pitahaya in Colombia.